2020
DOI: 10.1101/2020.06.04.135616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study of four SARS-CoV-2 Nucleic Acid Amplification Test (NAAT) platforms demonstrates that ID NOW performance is impaired substantially by patient and specimen type

Abstract: 14The advent of the COVID-19 pandemic in the United States created a unique situation 15 where multiple molecular diagnostic assays with various indications for use in the detection of 16 SARS-CoV-2 rapidly received Emergency Use Authorization by the FDA, were validated by 17 laboratories and utilized clinically, all within a period of a few weeks. We compared the 18 performance of four of these assays that were being evaluated for use at our institution: Abbott 19 RealTime m2000 SARS-CoV-2 Assay, DiaSor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A number of near-patient tests have been described. Some have not performed well, 12 and none have undergone testing under rigorous clinical trial conditions with real-world data on the impact on patient management. 13 , 14 , 15 , 16 , 17 Thorough, prospective evaluation for a high-consequence pathogen such as SARS-CoV-2 is particularly important, given the risks related to false positives or negatives in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…A number of near-patient tests have been described. Some have not performed well, 12 and none have undergone testing under rigorous clinical trial conditions with real-world data on the impact on patient management. 13 , 14 , 15 , 16 , 17 Thorough, prospective evaluation for a high-consequence pathogen such as SARS-CoV-2 is particularly important, given the risks related to false positives or negatives in the hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…The use of "convenience samples," particularly populations including patients who have been hospitalized after a diagnosis of COVID-19, may include more patients who are past their period of peak viral load compared to a sample of ambulatory patients first presenting for evaluation-such as those in our study who appeared for testing because of recent symptom onset. The two studies that met inclusion criteria for our review which had the lowest positive percent agreement between ID NOW and RT-PCR both included hospitalized patients, 13,17 although another study with very low concordance did not. 14 The conclusions from our clinical study are limited by a relatively small number of positive cases; nonetheless the high level of agreement with RT-PCR suggests that ID NOW is highly effective at identifying, or excluding, SARS-CoV-2 in a symptomatic ambulatory patient population.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the studies in our systematic review that showed discordance among assays to be most frequent when Ct values were relatively high (see Supplemental Materials). 3,4,[13][14][15][16] The ID NOW instructions for use (IFU, https://www.fda.gov/media/136525/download) have changed over time, but generally have called for samples to be tested no later than one hour after specimen acquisition and kept at room temperature during that period. The changes in the IFU have made it difficult to assess if published studies provided sufficient information to allow a determination that conformation to instructions for use was followed sufficiently.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%